Metacognition, psychopathology and daily functioning in adult ADHD. Issue 4 (21st April 2021) - Butzbach, Marah; Fuermaier, Anselm B. M.; Aschenbrenner, Steffen; Weisbrod, Matthias; Tucha, Lara; Tucha, Oliver
ABSTRACT: Objective: Previous research indicated that adults with ADHD may have deficits in metacognition, yet the evidence base is scarce. This study aims to explore the existence and nature of metacognitive deficits in adults with ADHD, how psychopathology (such as inattention and depression) may affect metacognition and whether metacognition may impact daily functioning in adults with ADHD. Method: Forty-six adult patients with ADHD and 46 controls completed questionnaires for metacognition, psychopathology and daily functioning (subjective assessment; self- and informant report). Participants performed two attention tests in a neuropsychological assessment. After test completion, participants were asked to evaluate their performance with the help of a visual aid and this self-evaluation of test performance was compared with their actual test performance (objective assessment). Results: Patients with ADHD reported large deficits in knowledge of cognition and medium deficits in regulation of cognition compared to controls. Self-evaluation of cognitive test performance revealed no significant deficits. Regression analyses revealed that psychopathology may explain a part of the variation in metacognition. Further regressions indicated that metacognition may account for a significant and meaningful proportion of variance in daily functioning, both self-rated and informant-rated. Conclusions: Current findings of compromised metacognitive functioning of adults with ADHD suggest that clinicians may not want to rely on patients' self-reports in the clinical assessment. Inattention predicted impairments in metacognition, pointing toward the importance of attention for awareness and metacognition. Finally, we recommend that metacognition is addressed in the treatment trajectory of patients with ADHD, given that aspects of metacognition were directly linked to impairments in daily functioning as rated by participants and their relatives.